The Recreational Frontier Ecotourism in Laos as Ecorational Instrumentality - Kleinod, Michael (Universitätsverlag Göttingen, 2017)
This study treats ecotourism in National Protected Areas of Lao PDR as a "recreational frontier" which instrumentalizes the recreation of human natures in capitalism's centers for that of nonhuman natures at capitalism's (closing) frontiers. This world-ecological practice of ecorational instrumentality - i.e. of nature domination in the name of "Nature" - presents a remedy for capitalism's crisis that is itself crisis-ridden, enacting a central tension of ecocapitalism: that between "conservation" and "development". This epistemic-institutional tension is traced through the preconditions, modes and effects of ecotourism in Laos by gradually zooming from the most general scale of societal nature relations into the most detailed intricacies of ecotouristic practice. The combination of Bourdieu, Marx and Critical Theory enables a systematic analysis of the recreational frontier as enactment of various contradictions deriving from the "false-and-real" Nature/Society dualism.